Eksistensi Akta Notariil dalam Pembatalan Akta Jual Beli Hak Atas Tanah yang Terdapat Cacat Administrasi (Studi Kasus di Kabupaten Kulon Progo) - Desiana Fauziah Yasmin (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2023)
The failure to conduct a certificate check in a Sale and Purchase Deed results in administrative defects, rendering it ineligible for registration with the Land Office. This situation causes losses to both the parties involved and the Land Deed Official who signed and recorded the deed in the Land Deed Official's Deed Register. Consequently, a new Sale and Purchase Deed and a notarial deed of cancellation for the defective Sale and Purchase Deed are required. This research aims to investigate the process of creating a notarial deed to cancel a Sale and Purchase Deed that contains administrative defects, as well as to determine the legal implications of the existence of the notarial deed of cancellation on land registration activities at the Kulon Progo District Land Office. This study is a normative-empirical research that employs both normative legal and empirical legal approaches. The subjects of the study are an informant from the Land Office of Kulon Progo District's Section for Determination of Rights and Registration, as well as a respondent from the Notary or Land Deed Official in the working area of Kulon Progo District. The research data is collected from primary and secondary sources, using literature review and interviews as data collection methods. The data analysis techniques used for this research are data collection, data presentation, and drawing conclusions. The research findings conclude that the notarial deed of cancellation can be valid and recognized in practice at Kulon Progo District.